RCRR VS GIST: A Quasi-Experimental Study On EFL Narrative Reading Comprehension In Indonesian Senior High School - Rara Cahya Aprilya; Gatot Subroto; Rona Elfiza (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Reading comprehension remains a major challenge in EFL learning because students must integrate textual information, vocabulary, inference, and background knowledge to understand narrative texts. This study aims to examine the effectiveness of the Read, Cover, Remember, Retell (RCRR) strategy on eleventh-grade students’ narrative reading comprehension at SMAN 2 Tanjungpinang. The research used a quantitative quasi-experimental design with a non-equivalent control group. The sample consisted of 72 students, divided into an experimental class taught using RCRR and a control class taught using GIST. Data were collected through pre-test and post-test multiple-choice reading comprehension tests covering main ideas, vocabulary in context, inference, and specific information. The data were analyzed using descriptive statistics, Shapiro-Wilk, Wilcoxon, and Mann-Whitney U tests. The findings show that both groups improved, but the RCRR class achieved higher post-test results and stronger learning gains. This study implies that RCRR is more effective for promoting active, structured, and reflective comprehension of narrative texts.